THE RELATIONSHIP BETWEEN RESILIENCE, EMOTIONAL INTELLIGENCE AND THEIR INFLUENCE ON PSYCHOLOGICAL WELLBEING: A STUDY WITH MEDICAL STUDENTS - Bano, Zaqia; Pervaiz, Saba (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find out the predictive relationship between resilience, emotional intelligence and psychological well being in medical students.Study Design: Cross sectional correlational study.Place and Duration of Study: Study was conducted at the department of Psychology, University of Gujrat, Sialkot Sub-campus, from Mar 2017 to Dec 2018.Methodology: A total of 200 medical students were recruited from different private and government medical colleges of Sialkot, Pakistan. The students of first professional year to final professional year between age ranges 19 years to 27 years were selected for the study. Cannor Devidson Resilience Scale, Trait Emotional Intelligence, Questionnaire-Short Form and psychological wellbeing scale-CPI, were used to find out the predictive relationship between resilience, emotional intelligence and psychological well-being in medical students.Results: Linear regression analysis was determined by using SPSS-21. Results showed significant predictive relationship between resilience and psychological well-being (R=0.315; R2=09; p